Dynamics of fractionated rhizosphere soil P and plant P uptake under maize/P-mobilizing legumes intercropping in strongly weathered soil of Tanzania. Issue 3 (4th May 2021) - Sugihara, Soh; Kawashita, Tomomi; Shitindi, Mawazo; Massawe, Boniface; Tanaka, Haruo
ABSTRACT: Intercropping with cereal and phosphorus (P)-mobilizing leguminous crops is a traditional agricultural practice in Sub-Saharan Africa. It is essential to evaluate the effect of intercropping (i.e., rhizosphere sharing) on fractionated rhizosphere soil P dynamics under the various soil P conditions and legumes, to improve the soil-plant P dynamics in this region. This study aimed to identify the effect of rhizosphere sharing of maize (MZ)/P-mobilizing legumes intercropping on fractionated rhizosphere soil P dynamics and plant P uptake under different P fertilization rates in strongly weathered cropland soil of Tanzania. We conducted 60-day MZ and P-mobilizing legumes intercropping pot experiments under different P-fertilized conditions (0, 50, and 100 kg P ha −1 ) with two legumes (pigeon pea (PP) and groundnut (GN)) by using three different root-separation treatments (no separation (NS) for rhizosphere sharing, nylon mesh separation (MS), and complete separation (CS)), to compare the effect of rhizosphere sharing in one pot. We evaluated the Hedley-fractionated P of rhizosphere soil and plant P uptake in each pot. We found that both P-efficient legumes did not clearly decrease the less labile P (NaOH-P) of rhizosphere soil in no P treatment, while these clearly decreased the less labile P in 100 kg P ha −1 treatment. It indicates that P-efficient legumes can solubilize the fertilized P but not native less labile P of the soil. The NS treatment increased the labile P of rhizosphere compared with CS by solubilizing the fertilized P, except for MZ/GN intercropping at 50 kg P ha −1 . Relative to CS, MZ/PP intercropping increased the total plant P uptake per pot (20%–40%) under P-fertilized conditions, whereas MZ/GN intercropping decreased it (17%) at 50 kg P ha −1 or showed no change at 100 kg P ha −1 . MZ/PP intercropping improved P fertilizer recovery efficiency, whereas MZ/GN intercropping did not. Enhanced P use efficiency through intercropping with P-mobilizing legumes is dependent on P-solubilizing characteristics of each P-mobilizing legume.